Relationship marketing in the Tanzanian - Davda, Prisha Chandrakant (2018)
The Banking Sector in Tanzania is one of the most competitive industries since it does not only compete with other banks but also with financial institutions. Therefore, banks in Tanzania have accentuated the need for effective management of relationships as a customer retention strategy. The primary objectives of this research are to study the benefits of Relationship Marketing for the customer and the organization from the organization`s perspective; to study the retention strategies and tactics used by banks in Tanzania to maintain its loyal customers; to assess the influence of dimensions of Relationship Marketing towards Customer Satisfaction and Retention. A mixed method approach was used for this study. A Semi structured interview was conducted with 12 Relationship Marketing Managers from various banks in Tanzania and a questionnaire was developed to which 303 customers participated. The data from the semi structured interview were analyzed using thematic analysis and the data collected from the survey were analyzed using a statistical software application called SPSS. The result of the qualitative study shows that both customers and banks benefit from Relationship Marketing efforts. The benefits for the banks are: customer satisfaction and increase in business and for the customers are: it builds trust and client recognition in the bank. The banks in Tanzania use various retention strategies and tactic. These are: good communication, social bonding, and promise fulfilment, offering of attractive products/services, conflict handling and prompt response and training of their employees. The result of the quantitative study shows that the five key dimensions, namely: trust for the bank, competence for the bank, customer care, security of the transaction and solution provider has a positive effect on customer satisfaction. Among all these 5 dimensions, trust for the bank plays an important role in customer satisfaction for this study. The study recommends that more banks in Tanzania should adopt the concept of relationship marketing as it benefits both, the bank and the customer. The banks should seek and use customer feedbacks to improve their product and service quality. Moreover, conflicts of the clients should be handled well and problems should be discussed openly with the customers.